THE ARABIC LANGUAGE AND THE KNOWLEDGE ECONOMY: REALITY AND CHALLENGES - Na'ima Sa'diyya; Mourad Terghini (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
This study addresses the contemporary challenges facing the Arabic language in the context of globalization and technological development, particularly within the framework of the knowledge economy. Accordingly, the study emphasizes the importance of understanding radical changes in linguistic communication patterns under this strategy, with a focus on monitoring and analyzing the technological and global influences on Arabic. The research also aims to explore the mechanisms and strategies necessary to preserve the status of the Arabic language and ensure its continuity as a living language capable of adapting in the digital age and within the knowledge economy. In the twenty-first century, the knowledge economy forms a central axis of economic and social development. In this context, the Arabic language represents a significant strategic tool that requires in-depth study to understand its impact and potential. This study seeks to analyze the complex relationship between the Arabic language and the knowledge economy, exploring current challenges and opportunities. The paper focuses on the role of Arabic as a key driver within the economic knowledge system, emphasizing contemporary digital and technological transformations. It also provides an in-depth analysis of challenges in technological, cultural, and educational fields under this strategy, offering a forward-looking perspective that underscores the importance of preserving linguistic and cultural identity to achieve linguistic and cultural security.